2018
DOI: 10.1071/ah16195
|View full text |Cite
|
Sign up to set email alerts
|

Patient satisfaction of telephone or video interpreter services compared with in-person services: a systematic review

Abstract: Objective This review was conducted to identify and synthesise the evidence around the use of telephone and video interpreter services compared with in-person services in healthcare. Methods A systematic search of articles published in the English language was conducted using PubMed, EMBASE, Cumulative Index to Nursing and Allied Health Literature (CINAHL), Cochrane Library, Database of Abstracts of Reviews of Effects (DARE), Joanna Briggs, Google Scholar and Google. Search terms included 'interpreter', 'patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(41 citation statements)
references
References 16 publications
1
38
1
1
Order By: Relevance
“…While there were differences in patient characteristics in terms of who received each modality of interpretation, after adjusting for these differences, overall quality remained similar across modalities with a trend toward VMI being a little better than in-person and telephone *** Cronbach alpha for five item scale = 0.964 (1=Poor, 2=Fair, 3=Good, 4=Very Good, and 5=Excellent) being a little worse. This is consistent with the literature on patient satisfaction with professional interpretation across modality 12 , and with another study which assessed patient perspective of overall encounter quality for visits with different professional interpretation modalities. 7 Although the literature on quality of interpretation by modality is limited, our group's previous work showed that from the interpreter perspective, telephone interpretation was adequate for simple information exchange, but VMI offered better communication for more complex clinical visits, 4 and from the physician's perspective, VMI and in-person interpretation offered similar quality of interpretation, although in-person interpretation allowed for more nuance particularly when addressing cultural differences.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…While there were differences in patient characteristics in terms of who received each modality of interpretation, after adjusting for these differences, overall quality remained similar across modalities with a trend toward VMI being a little better than in-person and telephone *** Cronbach alpha for five item scale = 0.964 (1=Poor, 2=Fair, 3=Good, 4=Very Good, and 5=Excellent) being a little worse. This is consistent with the literature on patient satisfaction with professional interpretation across modality 12 , and with another study which assessed patient perspective of overall encounter quality for visits with different professional interpretation modalities. 7 Although the literature on quality of interpretation by modality is limited, our group's previous work showed that from the interpreter perspective, telephone interpretation was adequate for simple information exchange, but VMI offered better communication for more complex clinical visits, 4 and from the physician's perspective, VMI and in-person interpretation offered similar quality of interpretation, although in-person interpretation allowed for more nuance particularly when addressing cultural differences.…”
Section: Discussionsupporting
confidence: 90%
“…[8][9][10][11] A systematic review of patient satisfaction with interpreter by modality also found that patients are generally satisfied with interpreters regardless of modality, as long as those interpreters are professionally trained. 12 While this previous literature suggests the importance of measuring interpreter quality and demonstrates patient satisfaction with professional interpretation, there remains a gap in detailed understanding of how the quality of interpreter-specific communication may differ across interpretation modality from a patient perspective. For patients with LEP, it is important to understand whether quality of professional interpretation in-person is preserved in remote modalities.…”
Section: Introductionmentioning
confidence: 99%
“…Video‐interpreting in a clinical context involves the use of TM with an interpreter located in a different location to the clinician and CALD patient to assist with medical consultations. Telephone and video‐interpreting were found to be just as effective as FTF interpreting, with similar levels of patient satisfaction (Joseph, Garruba, & Melder, ) in younger CALD individuals. Therefore, using alternative telecommunication modalities to deliver interpreter‐assisted health care may overcome the barriers of interpreter availability when diagnosing dementia in older people from CALD backgrounds.…”
Section: Introductionmentioning
confidence: 90%
“…There are some circumstances in which remote methods are preferred, 7,8 but many patients, interpreters, and providers express preference for in-person encounters. 9 Although current evidence does not conclusively identify a superior mode of interpretation in all settings, 10 remote tools can be difficult to use and depend on adequate wi-fi, variable wait time fluctuating with language availability, and inconsistent interpreter skillset. A comprehensive pilot study comparing remote and in-person interpretation modalities at the Cambridge Health Alliance identified situations poorly suited for telephone interpretation, including commotion in the room, procedures, and trying to communicate with multiple people, 7 all common features of labor and delivery.…”
Section: Scenariomentioning
confidence: 97%